FOOD AND MEDICINAL VALUE OF SOME FOREST SPECIES FROM BUENOSAIRES (ARGENTINA) - Sharry, S.; Abedini, W.; Cordal, M.A. Basiglio; Briones, V.; Roussy, L.; Stevani, R.; Galarco, S.; Adema, M. (Emirates Journal of Food and Agriculture, 2011)
To effectively use wild trees as food or active principles sources, we must to know their characteristics, as well as proper collection and preparation methods. In Argentina indigenous forest tree species provide goods and services such as firewood, fruits, timber, poles, fodder, environmental protection and amenities. The native forests of Buenos Aires province (Argentine) are strictly confined to the coastal strip of Río de la Plata (marginal forests and talares forests. Fig. 1) and to the Western region (caldén forests). Tree species found in the Talares and marginal forest include Celtis tala (tala), Scutia buxifolia (coronillo), Jodina rhombifolia (sombra de toro), Schinus longifolius (molle), Sambucus australis (sauco), Erythrina crista galli, Sesbania punicea (acacia mansa), Phytolacca tetramera (ombusillo) and Parkinsonia acculeata (cina cina), Salix humboldtiana (sauce), Citharexylum montevidensis (espina de bañado) between others. This species has different traditional and industry (medicinal, food, etc.) uses. There is little information on the biology and propagation systems of these native tree species. The different purposes they could be used for and the genetic variation between and within the species. This lack of knowledge could lead to irreversible loss of genetic diversity even before any study on variability and bioprospection is made. At the CEPROVE (Experimental Center of vegetative propagation, Faculty of Agronomy and Forestry, La Plata University) we are developing a germoplasm bank and research works in forest native species from ?Talares? and marginal forest using several tools, including biotechnology. The final objective is domesticated and put under culture of wild trees to obtain different products.